Adherence to care protocols for non-infection of the surgical site of the spine - Eliane Carlosso Krummenauer; Jane Dagmar Pollo Renner; Rochele Mosmann Menezes; Telmo Tiburcio Fortes Lima; Marcelo Carneiro (Universidade Federal de Santa Maria, 2021)
Objective: to evaluate adherence to treatment protocols for non-surgical site infection (NISC) of the spine and associated factors. Method: cross-sectional study conducted through the review of 60 medical records of patients undergoing spinal surgery from 2015 to 2019, its non-infection outcome and related conditions. The study was carried out in the first half of 2020. Results: some variables related to NISC were: antimicrobial prophylaxis from 30 to 60 min before surgery (RR= 0.97; p=0.026), normothermia (RR= 0.80; p =0.050), post-surgical hospitalization in the Intensive Care Unit (up to 3 days) (RR=2.00; p=0.040). The frequency of NISC was 83.3% (50/60) p= 0.728). Conclusion: only normothermia was a factor associated with non-infection for NISC in linear regression. It is noteworthy that adherence to work processes is essential to protect against infections, reduce adverse events and ensure safety.